Computer Network Specification for Distributed Spatial Data System - Agus Pribadi; I Wayan Astika; M. Arief Syafi’i (Seminar Nasional Aplikasi Teknologi Informasi (SNATI), 2006)
In recent years, spatial data and database become very important thing. Spatial data and database are stored into data and database server called data center. The last trend of spatial data and database management utilizes the concepts of data clearinghouse (DCH) and data warehousing (DWH). The Geographic Information System (GIS) can contain a wide variety of geographic data types originating from many diverse sources. Data source providers also come from various locations separately. The main issue of GIS project concerning to the data and information is currentness. In many cases, GIS projects consume a lot of the time to collect data inputs due to the distributed location of data. This condition decreases the currentness of GIS data used in the project. Another major development of recent years is in computer networks. The computer network can make many GIS data providers (server) interconnected. The most current utilization of computer network in the GIS is still used for data transfer and data visualization. The terminal simply provides a means for entering and displaying data for the computer.The objective of this research is to specify the computer network specification to support distributed spatial data processing based on GIS application. This system will be developed based on computer network infrastructure in Indonesia. The research methodology is field study, especially for computer network at Bakosurtanal and Biotrop – MIT as case. The result of this research is computer network specification that is used for spatial data transmission on distributed spatial data especially is in the internet connection.Based on current condition of physical computer network connection, the internet connection by peer-to-peer communication mode was be found unstable. The requested timed out signals were gotten 41.8% - 75.2% in the ping test of internet connection. The required time to transfer a GIS data file about 500 MByte was around 9 hours. Thereby, 100 KByte of GIS data needing data transfer time was around 6 seconds. The current physical connection technique for distributed spatial data using 128 Kbps bandwidth of internet connection, network cable category 5, is not recommended because the network connection is dissatisfactory. The new computer network specification has been arranged to solve the internet connection problem. It characteristics are: a) the intranet backbone uses 10 gigabit mode of fiber optic, b) using at least category 6 of twisted-pair cable for local computer network connection, c) the internet connection capacity (bandwidth) is recommended to apply at least 2 Mbps with stable connection, d) the recommendation of physical computer network topology is tree, e) utilizing a computerized network switch system to manage the computer network resources easier.